Correlation between alterations in degree of urbanization and the dynamics of agricultural land in Karawang regency - Wijdani, Firyal (EDP Sciences, 2023)
Karawang is part of the Jakarta-Bandung conurbation and is the largest rice producer there. Due to its strategic position and high agricultural potential, Karawang is interesting to be researched. This research has two aims: (1)to describe the degree of urbanization in Karawang and (2)to know the correlation between changes in the degree of urbanization in Karawang and the dynamics of rice fields. The classification of the degree of urbanization uses the level 2 classification by the European Union using built-up area and population data. Built-up area is extracted from land cover data and classified using Landsat imagery with Support Vector Machine classification. To find out the correlation, panel data regression is used. The results show that Karawang is dominated by the Suburban or Peri-Urban class. However, changes in the degree of urbanization occurred mostly in the central region, many of which became Urban Centers after 2000. The research revealed major transformations in land cover but surprisingly found no significant correlation between changes in the degree of urbanization and changes in agricultural land. These results emphasize the need for comprehensive policies that consider various economic, social, and policy factors related to the region's sustainable land management and urban planning. © 2023 EDP Sciences. All rights reserved.